2013
DOI: 10.1007/jhep10(2013)197
|View full text |Cite
|
Sign up to set email alerts
|

Quantum quench in matrix models: dynamical phase transitions, selective equilibration and the Generalized Gibbs Ensemble

Abstract: Quantum quench dynamics is considered in a one dimensional unitary matrix model with a single trace potential. This model is integrable and has been studied in the context of noncritical string theory. We find dynamical phase transitions, and study the role of the quantum critical point. In course of the time evolutions, we find evidence of selective equilibration for a certain class of observables. The equilibrium is governed by the Generalized Gibbs Ensemble (GGE) and differs from the standard Gibbs ensemble… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 111 publications
1
25
0
Order By: Relevance
“…Fully exact time-dependence and subsequent results on thermalization were obtained for free scalars and Fermions in 1+1 dimensions for mass quenches ending at zero mass in [14].In this paper, we will discuss quantum quench in a free Fermi gas in one space dimension, by using a large-N technique 4 . This subject was dealt with earlier in a paper [17] by two of the present authors, where it was shown how moments of the Fermion density approached thermalization from particular sudden quenches. Apart from studies of thermalization, several other dynamical aspects, such as the onset of shock fronts, have been studied in large-N non-interacting as well as interacting Fermi gases [18,19,20,21,22] (see also the Appendix A) ; finite-N corrections have been studied in [23].The importance of the large-N limit is that the Fermions are described by a semiclassical fluid in the phase space.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Fully exact time-dependence and subsequent results on thermalization were obtained for free scalars and Fermions in 1+1 dimensions for mass quenches ending at zero mass in [14].In this paper, we will discuss quantum quench in a free Fermi gas in one space dimension, by using a large-N technique 4 . This subject was dealt with earlier in a paper [17] by two of the present authors, where it was shown how moments of the Fermion density approached thermalization from particular sudden quenches. Apart from studies of thermalization, several other dynamical aspects, such as the onset of shock fronts, have been studied in large-N non-interacting as well as interacting Fermi gases [18,19,20,21,22] (see also the Appendix A) ; finite-N corrections have been studied in [23].The importance of the large-N limit is that the Fermions are described by a semiclassical fluid in the phase space.…”
mentioning
confidence: 76%
“…where we have used (17). Since the second terms would be suppressed at large t through the p integral due to the oscillation, we would obtain…”
Section: U(x P T) In V = 0 Casementioning
confidence: 99%
See 1 more Smart Citation
“…See Refs. [59][60][61][62][63][64][65][66] for more details in this direction. In this context we are interested in this specific type of mass parametrization as the corresponding equivalent version of Schrödinger quantum mechanical problem can easily solvable.…”
Section: Creation Of New Massive Particlementioning
confidence: 99%
“…In the standard WKB approximation the total solution can be recast in the following form: 66) where D 1 and D 2 are two arbitrary integration constants, which depend on the choice of the initial condition during WKB approximation at early and late time scale. In the present context u k (η) andū k (η) are defined as…”
Section: Axion-massive Particle Correspondencementioning
confidence: 99%